Nocebo effects from negative product information: when information hurts, paying money could heal. Issue 1 (8th January 2018) - Mukherjee, Sumitava; Sahay, Arvind
Abstract : Purpose: This research aimed to find whether information about a product can give rise to negative perceptions even in inert situations (nocebo effects), and to understand how price levels impact such judgments. Design/methodology/approach: In all experiments, participants were exposed to negative product information in the form of potential side-effects. In an initial study, a higher non-discounted versus a discounted price frame was presented for a health drink after customers were exposed to negative aspects. Then, in experiment 1, price (high vs low) and exposure to information (no information vs negative information) was manipulated for skin creams where participants physically evaluated the cream. In experiment 2, price was manipulated at three levels (low, high, discounted) orthogonally with product information (no negative information vs with negative information) to get a more nuanced understanding. Findings: In the initial study, after exposure to negative information, the non-discounted group had more positive ratings for the drink. Study 1 showed that reading about negative information resulted in a nocebo effect on perception of dryness (side-effect). Moreover, when no information was presented, perception of dryness by low and high price groups were similar but in the face of negative information, perception of dryness by low-price group was more pronounced compared to a high-price group. Study 2 conceptually replicated the effect and also confirmed that not only discounts (commonly linked with product quality), but absolute price levels also show a similar effect. Practical implications: Nocebo effects have been rarely documented in consumer research. This research showed how simply reading generically about potential side effects gives rise to nocebo effects. In addition, even though marketers might find it tempting to lower prices when there is negative information about certain product categories, such an action could backfire. Originality/value: To the best of our knowledge, the link between observable nocebo effects and its link with pricing actions is a novel research thread. We were able to show a nocebo effect on product perception after reading about negative information and also find that a higher price can mitigate the nocebo effect to some extent.